2013
DOI: 10.1371/journal.pone.0078731
|View full text |Cite
|
Sign up to set email alerts
|

Metabonomics Study of the Therapeutic Mechanism of Gynostemma pentaphyllum and Atorvastatin for Hyperlipidemia in Rats

Abstract: Gynostemma pentaphyllum (GP) is widely used for the treatment of diseases such as hyperlipidemia, fatty liver and obesity in China, and atorvastatin is broadly used as an anti-hyperlipidemia drug. This research focuses on the plasma and liver metabolites in the following four groups of rats: control, a hyperlipidemia model, a hyperlipidemia model treated with GP and a hyperlipidemia model treated with atorvastatin. Using 1H-NMR-based metabonomics, we elucidated the therapeutic mechanisms of GP and atorvastatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 35 publications
2
50
0
1
Order By: Relevance
“…Both aspartic acid and glutamine are glucogenic amino acid, and their levels in high‐fat diet decreased. It suggested that aspartic acid and glutamine were transformed to α‐keto acid, and metabolized to glucose via gluconeogenesis (Wang et al., ). Meanwhile, ammonia is produced by deamination of amino acids and mainly formed urea in liver because of its toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Both aspartic acid and glutamine are glucogenic amino acid, and their levels in high‐fat diet decreased. It suggested that aspartic acid and glutamine were transformed to α‐keto acid, and metabolized to glucose via gluconeogenesis (Wang et al., ). Meanwhile, ammonia is produced by deamination of amino acids and mainly formed urea in liver because of its toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…3 Angka penderita penyakit jantung di Indonesia mencapai 2,6 juta pada tahun 2013, sedangkan penderita strok mencapai 530.000 orang. 4 Pada keadaan ini pengobatan lini pertama dalam tata laksana dislipidemia menggunakan obat golongan statin contohnya simvastatin. 5 Akan tetapi, pada pengobatan jangka panjang akan dapat menyebabkan efek samping seperti rabdomiolisis, mialgia, miositis, meningkatkan risiko kanker, strok hemoragik, dan gangguan kognitif.…”
Section: Pendahuluanunclassified
“…Hyperlipidemia is mainly manifested in elevated contents of triglycerides, total cholesterol (TC) and low‐density‐lipoprotein cholesterol (LDL‐C) as well as decreased level of high‐density‐lipoprotein cholesterol (HDL‐C) in plasma as a general metabolic syndrome (Yan Zhang, Wang, Jin, Yang, & Zhou, ). Hyperlipidemia is a significant factor leading to atherosclerosis and cardiovascular complications and often causes coronary artery disease, stroke and myocardial infarction (Miao Wang et al, ). Hyperlipidemia and its complications are the primary cause of death in the world.…”
Section: Introductionmentioning
confidence: 99%